Hardness testing methods: Brinell, Rockwell, Vickers. Book 1. Practical work. Laboratory assignments 1–12 : methodological instructions - Moshchenok, Vasyl (Independently published, 2025)
Book Hardness testing methods: Brinell, Rockwell, Vickers. Book 1 is devoted to practical work on determining the hardness of materials and contains a detailed description of the three main measurement methods - Brinell, Rockwell and Vickers. The first chapter describes the Brinell method for determining steel hardness in accordance with ISO 6506-1:2019. It then discusses the selection of Brinell hardness test conditions for different materials. The following sections cover the Rockwell method, both with a conical and spherical indenter, in accordance with ISO 6508-1:2019. The Vickers method is presented using a diamond pyramid and includes measurements of low-load hardness and microhardness. Separate chapters are devoted to the determination of surface and projection hardness using Brinell, Rockwell, and Vickers instruments. The book is a practical guide for engineers, researchers and students working in the field of materials science and quality control.
Keywords: hardness testing; brinell method; rockwell method; vickers method; materials science; indenter; microhardness; quality control; steel; iso 6506; iso 6508; materials testing; surface hardness; engineering